Modified glass powder for low-silver-content conductive silver paste as well as preparation method and application of modified glass powder

By using the modified glass powder to load the reinforcement technology of nano -silver and sub -glass powder in the conductive silver pulp, the problem of high cantiscar cost and traditional sintering technology of the battery is solved, and the low silver content conductive silver pulp is in LECO Excellent performance under sintering technology.

CN119371108APending Publication Date: 2025-01-28FOSHAN HAOYU XINNENG TECH CO LTD

Patent Information

Application Number
CN202411375698.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing conductive silver paste has a high silver powder mass ratio during the preparation process, resulting in excessive cost. At the same time, traditional high-temperature sintering technology causes damage to the battery and is difficult to effectively reduce metal-induced recombination.

Method used

The modified glass powder is adopted to load nano -silver on the surface of the main glass powder through the melting cold extract and alcohol reduction method, combined with the complexity of the auxiliary glass powder, forming a low silver content conductive silver slurry, which is suitable for the low -fever temperature conditions of LECO sintering technology.

Benefits of technology

Under the lower silver content, the battery has achieved low contact resistance, high -opening voltage and high -light transformation efficiency, reducing production costs, and avoiding traditional sintering technology damage to batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068618420000051
    Figure BDA0005068618420000051
  • Figure BDA0005068618420000061
    Figure BDA0005068618420000061
  • Figure BDA0005068618420000071
    Figure BDA0005068618420000071
Patent Text Reader

Abstract

The invention relates to the technical field of H01B1 / 16, in particular to modified glass powder for low-silver-content conductive silver paste and a preparation method and application of the modified glass powder. The silver-loaded modified glass powder at least comprises the following components: main glass powder, an alcoholic solution and silver-containing powder; the main glass powder at least comprises the following components in parts by weight: 1-10 parts of aluminum oxide, 15-20 parts of silicon oxide, 1-10 parts of zinc oxide, 40-65 parts of lead oxide, 10-30 parts of boron oxide, 10-15 parts of bismuth oxide and 1-5 parts of silver oxide, so that the requirements of low contact resistance, high open-circuit voltage and high photoelectric conversion efficiency of a battery at a lower sintering temperature by an LECO sintering technology are met; the conductive paste is suitable for conductive paste with lower silver content, and better battery performance is taken into account while the cost is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of H01B1 / 16, and in particular to a modified glass powder for conductive silver paste with low silver content, and a preparation method and application thereof. Background Art

[0002] With the rapid development of crystalline silicon solar cells, N-type TOPCon solar cells with advantages such as high photoelectric conversion efficiency, high cost performance, low attenuation, and high yield have gradually become the mainstream products in the industry. In order to further improve the performance of TOPCon cells, the industry has begun to promote the use of the new LECO (Laser Enhanced Contact Optimization) sintering technology to replace the traditional high-temperature sintering technology. Traditional high-temperature sintering not only damages the battery, but also easily causes more serious metal-induced recombination, which will greatly reduce the efficiency of the battery. The LECO process is to irradiate the cell with a high-intensity laser and apply a bias voltage of 10V or more. The resulting local current of several amperes will significantly reduce the contact resistance between the metal and the semiconductor. The essence of the LECO process is actually to enhance the contact ability of the silver paste with the battery or circuit, reduce the contact resistance, and minimize the damage to the passivation layer of the cell. These factors can greatly improve the photoelectric conversion efficiency of crystalline silicon cells, and can achieve a conversion efficiency increase of about 0.2 to 0.6%. At present, in the preparation process of the conductive silver paste used in N-type TOPCon batteries, the silver powder mass ratio reaches more than 89%, which accounts for the vast majority of the cost of the entire conductive silver paste, resulting in excessively high manufacturing costs of the silver paste. In order to reduce costs, the conductive silver paste is also developing towards a lower silver powder content.

[0003] In order to match the low sintering temperature of LECO and further reduce production costs, it is necessary to design the conductive silver paste more reasonably. This has extremely important research value and practical application value for further improving the efficiency of N-type TOPCon cells. A Chinese patent (authorization announcement number CN 114656154 B) discloses a glass powder, a back silver paste for high-performance PERC cells and a preparation method thereof. Although the content of spherical silver powder in the back silver paste is 60.8wt%, its photoelectric conversion efficiency is as early as 22.827-22.870%, which needs to be further improved. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a modified glass powder for low-silver content conductive silver paste, which meets the requirements of LECO sintering technology to achieve low contact resistance, high open circuit voltage and high photoelectric conversion efficiency of the battery at a lower sintering temperature, and is suitable for conductive paste with lower silver content, saving costs while taking into account better battery performance.

[0005] On the one hand, the present invention provides a modified glass powder for low-silver content conductive silver paste, which is composed of silver-loaded modified glass powder and auxiliary glass powder; the silver-loaded modified glass powder at least includes the following components: main glass powder, alcohol solution, and silver-containing powder; in parts by weight, the main glass powder at least includes the following components: 1-10 parts of aluminum oxide, 15-20 parts of silicon oxide, 1-10 parts of zinc oxide, 40-65 parts of lead oxide, 10-30 parts of boron oxide, 10-15 parts of bismuth oxide, and 1-5 parts of silver oxide.

[0006] As a preferred technical solution, the method for preparing the main glass powder at least comprises the following steps:

[0007] (1) accurately weighing aluminum oxide, silicon oxide, zinc oxide, lead oxide, boron oxide, bismuth oxide, and silver oxide, placing them in a mixer, stirring and mixing, and then transferring them to a platinum crucible;

[0008] (2) heating the muffle furnace to 1100-1200° C. according to the set program, placing the platinum crucible in the preheated muffle furnace, and smelting at high temperature for 20-40 min; then taking out the platinum crucible, placing the resulting melt in a cooling roller for cold rolling;

[0009] (3) placing the cold-rolled glass sheet in a planetary ball mill for ball milling, the ball milling speed is 150-500 rpm, the ball milling time is 90-180 min, and the mass ratio of the grinding ball to the cold-rolled product in the ball milling process is (3-7):1;

[0010] (4) The glass powder after ball milling is subjected to coarse screening treatment, and the coarsely screened glass powder is placed in a jet mill for secondary grinding treatment to obtain the obtained product. The jet mill pressure is 0.8-1.2 MPa, and the processing time is 5-15 min.

[0011] As a preferred technical solution, the D50 particle size of the main glass powder is 1.0-3.0 μm, preferably 1.5-2.5 μm, and more preferably 1.8-2.0 μm.

[0012] As a preferred technical solution, the method for preparing the silver-loaded modified glass powder comprises at least the following steps:

[0013] S1. Dispersing the main glass powder into the alcohol solution, mechanically stirring for 10-30 minutes to obtain a white suspension, then adding the silver-containing powder to the white suspension, and stirring at 15-30° C. for 15-40 minutes to obtain a mixture;

[0014] S2. Ultrasonicate the mixture at 15-30°C for 5-15 minutes, then place the container containing the mixture in a water bath at 70-80°C for 30-90 minutes of precipitation, with continuous stirring during the precipitation process; as the reaction proceeds, the color of the mixture gradually changes from white to brown or even dark brown;

[0015] S3. The solvent is then separated by centrifugation, and then washed with deionized water. The brown precipitate is dried in an oven at 60-70° C. for at least 3 hours to obtain agglomerated glass, which is then sieved to obtain silver-loaded modified glass powder.

[0016] As a preferred technical solution, the alcohol solution is a mixed solution of water and at least one of ethylene glycol, propylene glycol, ethanol and methanol.

[0017] As a preferred technical solution, the silver-containing powder is at least one of silver nitrate, silver sulfate and silver chloride.

[0018] As a preferred technical solution, the silver-containing powder includes 0.1-0.5 parts of silver nitrate and 0.1-0.2 parts of silver sulfate by weight.

[0019] As a preferred technical solution, the concentration of the main glass powder in the alcohol solution is 0.1-1 g / mL, preferably 0.2-0.5 g / mL, and more preferably 0.2-0.3 g / mL.

[0020] As a preferred technical solution, the mass ratio of the main glass powder to the silver-containing powder is (10-15):(0.1-1), preferably (10-15):(0.3-0.6).

[0021] As a preferred technical solution, the secondary glass powder includes at least the following components by weight: 1-10 parts of aluminum oxide, 20-45 parts of silicon oxide, 1-5 parts of zinc oxide, 30-55 parts of lead oxide, 10-20 parts of boron oxide, and 10-15 parts of bismuth oxide.

[0022] As a preferred technical solution, the method for preparing the secondary glass powder at least comprises the following steps:

[0023] 1) Accurately weigh aluminum oxide, silicon oxide, zinc oxide, lead oxide, boron oxide, and bismuth oxide, place them in a mixer, stir and mix them, and then transfer them to a platinum crucible;

[0024] 2) According to the set program, the temperature of the muffle furnace is raised to 1100-1200°C, and the platinum crucible is placed in the preheated muffle furnace for high-temperature smelting for 20-40 minutes; then the platinum crucible is taken out, and the obtained melt is placed in a cooling roller for cold rolling treatment;

[0025] 3) placing the cold-rolled glass sheet in a planetary ball mill for ball milling, the ball milling speed is 150-500 rpm, the ball milling time is 90-180 min, and the mass ratio of the grinding ball to the cold-rolled product in the ball milling process is (3-7):1;

[0026] 4) The glass powder after ball milling is subjected to coarse screening treatment, and the coarsely screened glass powder is placed in a jet mill for secondary grinding treatment to obtain the obtained product. The jet mill pressure is 0.8-1.2 MPa, and the processing time is 5-15 min.

[0027] As a preferred technical solution, the D50 particle size of the secondary glass powder is 1.0-3.0 μm, preferably 1.5-2.5 μm, and more preferably 1.8-2.0 μm.

[0028] On the other hand, the present invention provides a method for preparing modified glass powder for low-silver content conductive silver paste, which comprises at least the following steps: mixing the silver-loaded modified glass powder and the auxiliary glass powder in a mass ratio of (3-5):1 to obtain the result.

[0029] In order to match the low sintering temperature of LECO and further reduce the production cost for optimization, the present invention synthesizes a modified glass powder for low-silver content conductive silver paste by melt quenching combined with alcohol reduction method to achieve further efficiency improvement of N-type TOPCon battery.

[0030] Specifically, the present invention adopts a specific content of aluminum oxide, silicon oxide, zinc oxide, lead oxide, boron oxide, bismuth oxide, and silver oxide to prepare a main glass powder by a melt cold extraction method, and the main glass powder is loaded with nanosilver on its surface by an "alcohol reduction method". The loaded nano-scale silver particles can achieve good ohmic contact with the battery silicon substrate under the condition of lower silver content. Such excellent contact ability can ensure a lower series resistance of the battery under the condition of reducing the silver content of the conductive silver paste.

[0031] Furthermore, by compounding the auxiliary glass powder containing a specific content of aluminum oxide, silicon oxide, zinc oxide, lead oxide, boron oxide, and bismuth oxide, the two glass powders can synergistically obtain appropriate etching ability and suitable glass viscosity-temperature characteristics. Specifically, the main glass loaded with nanosilver in the present invention has a lower glass transition temperature and due to the effect of nanosilver particles and the introduction of silver oxide in the main glass itself, the electrode can be better contacted with the battery substrate; and the auxiliary glass with a higher glass transition temperature can reduce the damage to the battery passivation layer, thereby ensuring the stability of the battery open circuit voltage.

[0032] The silver-loaded modified glass powder and the sub-double glass powder double glass design of the present invention can ensure that the high open circuit voltage, low series resistance and high photoelectric conversion efficiency of the battery can be achieved under the conditions of lower sintering temperature and lower silver content of the LECO sintering technology.

[0033] A third aspect of the present invention provides an application of modified glass powder for low-silver content conductive silver paste, which is applied to the preparation of low-silver content TOPCon battery fine grid silver paste.

[0034] As a preferred technical solution, the raw materials for preparing the low-silver content TOPCon battery fine grid silver paste include at least: 80-88 parts of silver powder, 1-3 parts of modified glass powder, 5-10 parts of organic carrier, and 1-3 parts of solvent, by weight.

[0035] Preferably, the organic carrier comprises, by mass percentage, 2-5% ethyl cellulose, 1-5% acrylic resin, 10-30% diethylene glycol methyl ether, 10-20% butyl carbitol acetate, 0.1-2% lecithin, and the balance is made up by terpineol.

[0036] Preferably, the solvent is alcohol lipid dodecahydrate.

[0037] The preparation method of the TOPCon battery fine grid silver paste with low silver content is as follows: silver powder, modified glass powder, organic carrier and solvent are mixed to obtain the paste.

[0038] Beneficial Effects

[0039] 1. The present invention provides a modified glass powder for low-silver content conductive silver paste, which meets the requirements of LECO sintering technology to achieve low contact resistance, high open circuit voltage and high photoelectric conversion efficiency of the battery at a lower sintering temperature. It is suitable for conductive paste with lower silver content, saving costs while taking into account better battery performance.

[0040] 2. The present invention uses specific contents of aluminum oxide, silicon oxide, zinc oxide, lead oxide, boron oxide, bismuth oxide, and silver oxide to prepare a main glass powder by a melt cold extraction method, and loads nanosilver on the surface of the main glass powder by an "alcohol reduction method". The loaded nano-scale silver particles can achieve good ohmic contact with the battery silicon substrate under the condition of lower silver content. Such excellent contact ability can ensure a lower series resistance of the battery under the condition of reducing the silver content of the conductive silver paste.

[0041] 3. By compounding the secondary glass powder containing specific content of aluminum oxide, silicon oxide, zinc oxide, lead oxide, boron oxide and bismuth oxide, the synergistic effect of the two glass powders can obtain appropriate etching ability and suitable glass viscosity-temperature characteristics.

[0042] 4. The main glass loaded with nanosilver in the present invention has a lower glass transition temperature and due to the effect of nanosilver particles and the introduction of silver oxide in the main glass itself, the electrode can be better contacted with the battery substrate; and the secondary glass with a higher glass transition temperature can reduce the damage to the battery passivation layer, thereby ensuring the stability of the battery open circuit voltage.

[0043] 5. The silver-loaded modified glass powder and the sub-double glass powder double glass design of the present invention can ensure that the high open circuit voltage, low series resistance and high photoelectric conversion efficiency of the battery can be achieved under the conditions of lower sintering temperature and lower silver content of the LECO sintering technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1-3 This is the SEM characterization image of silver-loaded modified glass powder. DETAILED DESCRIPTION

[0045] Examples 1-4

[0046] Embodiments 1-4 of the present invention provide a modified glass powder for conductive silver paste with low silver content. The modified glass powder for conductive silver paste with low silver content provided in Embodiment 1 consists of main glass powder and auxiliary glass powder; the modified glass powder for conductive silver paste with low silver content provided in Embodiments 2-4 consists of silver-loaded modified glass powder and auxiliary glass powder; the silver-loaded modified glass powder comprises the following components: main glass powder, alcohol solution, and silver-containing powder; the raw materials for preparing the main glass powder and auxiliary glass powder in each embodiment are shown in Table 1 in parts by weight.

[0047] Table 1

[0048]

[0049]

[0050] The method for preparing the main glass powder comprises the following steps:

[0051] (1) accurately weighing aluminum oxide, silicon oxide, zinc oxide, lead oxide, boron oxide, bismuth oxide, and silver oxide, placing them in a mixer, stirring and mixing, and then transferring them to a platinum crucible;

[0052] (2) According to the set program, the temperature of the muffle furnace is raised from 25°C to 1100°C at a rate of 10°C / min, and the platinum crucible is placed in the preheated muffle furnace for high-temperature smelting for 30 minutes; then the platinum crucible is taken out, and the resulting melt is placed on a cooling roller for cold rolling;

[0053] (3) placing the cold-rolled glass sheet in a planetary ball mill for ball milling, the ball milling speed is 350 rpm, the ball milling time is 180 min, and the mass ratio of the grinding ball to the cold-rolled product in the ball milling process is 5:1;

[0054] (4) The glass powder after ball milling is subjected to coarse screening treatment (200 mesh screen), and the coarsely screened glass powder is placed in a jet mill for secondary grinding treatment. The jet mill pressure is 1.2 MPa and the processing time is 10 min.

[0055] The main glass powder has a D50 particle size of 1.8 to 2.0 μm, and a D97 particle size of 2.2 to 2.8 μm.

[0056] The method for preparing the silver-loaded modified glass powder comprises the following steps:

[0057] S1. Dispersing the main glass powder into the alcohol solution, mechanically stirring for 20 minutes to obtain a white suspension, then adding the silver-containing powder to the white suspension, and stirring at 25° C. for 30 minutes to obtain a mixture;

[0058] S2. The mixture was ultrasonically treated at 25°C for 10 min, and then the container containing the mixture was placed in a water bath at 75°C for 60 min of deposition, with continuous stirring during the deposition process; as the reaction proceeded, the color of the mixture gradually changed from white to brown or even dark brown;

[0059] S3. The solvent is then separated by centrifugation, and then washed with deionized water. The obtained brown precipitate is dried in an oven at 65° C. for 5 h to obtain agglomerated glass, which is then sieved (200 mesh) to obtain silver-loaded modified glass powder.

[0060] The alcohol solution is a mixed solution of water and ethylene glycol in a mass ratio of 1:9.

[0061] In parts by weight, the silver-containing powder includes 0.3 parts of silver nitrate and 0.1 parts of silver sulfate.

[0062] The concentration of the main glass powder in the alcohol solution is 0.25 g / mL.

[0063] The mass ratio of the main glass powder to the silver-containing powder is 10:0.4.

[0064] The method for preparing the secondary glass powder comprises the following steps:

[0065] 1) Accurately weigh aluminum oxide, silicon oxide, zinc oxide, lead oxide, boron oxide, and bismuth oxide, place them in a mixer, stir and mix them, and then transfer them to a platinum crucible;

[0066] 2) According to the set program, the temperature of the muffle furnace is raised from 25°C to 1100°C at a rate of 10°C / min, and the platinum crucible is placed in the preheated muffle furnace for high-temperature smelting for 30 minutes; then the platinum crucible is taken out, and the resulting melt is placed in a cooling roller for cold rolling treatment;

[0067] 3) placing the cold-rolled glass sheet in a planetary ball mill for ball milling, the ball milling speed is 350 rpm, the ball milling time is 180 min, and the mass ratio of the grinding ball to the cold-rolled product in the ball milling process is 5:1;

[0068] 4) The glass powder after ball milling was subjected to coarse screening treatment (200 mesh screen), and the coarsely screened glass powder was placed in a jet mill for secondary grinding treatment. The jet mill pressure was 1.2 MPa and the processing time was 10 min.

[0069] The secondary glass powder has a D50 particle size of 1.8 to 2.0 μm, and a D97 particle size of 2.2 to 2.8 μm.

[0070] The method for preparing a modified glass powder for a low-silver content conductive silver paste provided in Example 1 is as follows: main glass powder and auxiliary glass powder are mixed in a mass ratio of 3:1.

[0071] The preparation method of the modified glass powder for low-silver content conductive silver paste provided in Example 2-4 is as follows: the silver-loaded modified glass powder and the auxiliary glass powder are mixed in a mass ratio of 3:1.

[0072] Application Examples 1-4

[0073] Application Examples 1-4 of the present invention provide a TOPCon battery fine grid silver paste with a low silver content, and the formula is shown in Table 2 in parts by weight.

[0074] Table 2

[0075]

[0076]

[0077] Calculated by mass percentage, the organic carrier includes: 2.5% of ethyl cellulose, 2% of acrylic resin, 60% of pineneol, 20% of diethylene glycol methyl ether, 14.5% of butyl carbitol acetate, and 1% of lecithin.

[0078] The preparation method of the TOPCon battery fine grid silver paste with low silver content is as follows: silver powder, modified glass powder, organic carrier and solvent are mixed to obtain the paste.

[0079] Application comparison example

[0080] The control example of the present invention is the silver paste DK71A specially used for N-type TOPcon batteries commercially available from Wuxi Dike Electronic Materials Co., Ltd.

[0081] Performance Testing

[0082] 1. SEM characterization of silver-loaded modified glass powder. See Figure 1-3As can be seen from the picture, the surface of the modified glass powder is successfully loaded with nanosilver, and the nanosilver is spherical.

[0083] 2. The silver paste provided in Application Examples 1-4 and Application Comparative Examples was respectively printed on the front of 182 mm × 182 mm TOPCon cells by screen printing, and the silver paste was uniformly printed on the back. Application Examples 1-4 and the Comparative Examples were sintered at a peak temperature of 700°C and light injected using a sintering furnace, and then passed through a LECO device for laser-assisted sintering to obtain cells 1-5. The photoelectric conversion efficiency (Eff), open circuit voltage (Uoc), short circuit current (Isc), fill factor (FF), series resistance (Rser), and parallel resistance (Rsh) of cells 1-5 were tested by current-voltage performance. The test results are shown in Table 3.

[0084] Table 3

[0085] serial number Eff / % Uoc / V Isc / A FF / % Rser / Ω Rsh / Ω Battery Cell 1 24.57 0.732 13.88 83.91 0.00201 1970 Battery Cell 2 25.88 0.736 14.38 85.58 0.00101 1920 Battery Cell 3 25.68 0.734 14.39 85.01 0.00147 1990 Battery Cell 4 25.27 0.737 14.11 84.89 0.00184 1944 Battery Cell 5 25.70 0.735 14.38 85.11 0.00140 1937

[0086] By analyzing the above table, it can be seen that the main glass powder of battery cell 1 has not been modified by loading nano silver oxide, and it is not easy to form a good contact under low silver content conditions, which makes the battery series resistance larger and the fill factor lower. The battery efficiency of battery cell 2 has certain advantages over the control example battery cell 5 with a higher silver content, mainly because the series resistance is lower and the open circuit voltage is slightly higher. Battery cell 3 may have an excessive load of nano silver, which increases the battery series resistance. Battery cell 4 does not introduce silver oxide into the main glass powder, which increases the battery series resistance and reduces the fill factor.

[0087] The above description is a preferred embodiment of the present invention and is not intended to limit the present invention. Without departing from the principles described in the present invention, various improvements and modifications made should be included in the protection scope of the present invention.

Claims

1. A modified glass powder for low silver content conductive silver paste, characterized in that: It is composed of silver-loaded modified glass powder and auxiliary glass powder; the silver-loaded modified glass powder at least includes the following components: main glass powder, alcohol solution, silver-containing powder; The main glass powder includes at least the following components by weight: 1-10 parts of aluminum oxide, 15-20 parts of silicon oxide, 1-10 parts of zinc oxide, 40-65 parts of lead oxide, 10-30 parts of boron oxide, 10-15 parts of bismuth oxide, and 1-5 parts of silver oxide.

2. The modified glass powder for low silver content conductive silver paste according to claim 1, characterized in that: The method for preparing the main glass powder at least comprises the following steps: (1) accurately weighing aluminum oxide, silicon oxide, zinc oxide, lead oxide, boron oxide, bismuth oxide, and silver oxide, placing them in a mixer, stirring and mixing, and then transferring them to a platinum crucible; (2) heating the muffle furnace to 1100-1200° C. according to the set program, placing the platinum crucible in the preheated muffle furnace, and smelting at high temperature for 20-40 min; then taking out the platinum crucible, placing the resulting melt in a cooling roller for cold rolling; (3) placing the cold-rolled glass sheet in a planetary ball mill for ball milling, the ball milling speed is 150-500 rpm, the ball milling time is 90-180 min, and the mass ratio of the grinding ball to the cold-rolled product in the ball milling process is (3-7):1; (4) The glass powder after ball milling is subjected to coarse screening treatment, and the coarsely screened glass powder is placed in a jet mill for secondary grinding treatment to obtain the obtained product. The jet mill pressure is 0.8-1.2 MPa, and the processing time is 5-15 min.

3. The modified glass powder for low silver content conductive silver paste according to claim 2, characterized in that: The D50 particle size of the main glass powder is 1.0-3.0 μm.

4. The modified glass powder for low silver content conductive silver paste according to claim 3, characterized in that: The method for preparing the silver-loaded modified glass powder comprises at least the following steps: S1. Dispersing the main glass powder into the alcohol solution, mechanically stirring for 10-30 minutes to obtain a white suspension, then adding the silver-containing powder to the white suspension, and stirring at 15-30° C. for 15-40 minutes to obtain a mixture; S2. Ultrasonicate the mixture at 15-30°C for 5-15 minutes, then place the container containing the mixture in a water bath at 70-80°C for 30-90 minutes of precipitation, with continuous stirring during the precipitation process; as the reaction proceeds, the color of the mixture gradually changes from white to brown or even dark brown; S3. The solvent is then separated by centrifugation, and then washed with deionized water. The brown precipitate is dried in an oven at 60-70° C. for at least 3 hours to obtain agglomerated glass, which is then sieved to obtain silver-loaded modified glass powder.

5. The modified glass powder for low silver content conductive silver paste according to claim 4, characterized in that: The alcohol solution is a mixed solution of water and at least one of ethylene glycol, glycerol, ethanol and methanol.

6. The modified glass powder for low silver content conductive silver paste according to claim 5, characterized in that: The silver-containing powder is at least one of silver nitrate, silver sulfate and silver chloride.

7. The modified glass powder for low silver content conductive silver paste according to claim 6, characterized in that: In parts by weight, the secondary glass powder comprises at least the following components: 1-10 parts of aluminum oxide, 20-45 parts of silicon oxide, 1-5 parts of zinc oxide, 30-55 parts of lead oxide, 10-20 parts of boron oxide, and 10-15 parts of bismuth oxide.

8. A method for preparing the modified glass powder for low silver content conductive silver paste according to any one of claims 1 to 7, characterized in that: At least the following steps are included: The modified glass powder loaded with silver and the auxiliary glass powder are mixed in a mass ratio of (3-5):1 to obtain the obtained product.

9. An application of the modified glass powder for low silver content conductive silver paste according to any one of claims 1 to 7, characterized in that: Used in the preparation of fine grid silver paste for TOPCon cells with low silver content.

10. The use of the modified glass powder for low silver content conductive silver paste according to claim 9, characterized in that: By weight, the raw materials for preparing the low-silver-content TOPCon battery fine grid silver paste include at least: 80-88 parts of silver powder, 1-3 parts of modified glass powder, 5-10 parts of organic carrier, and 1-3 parts of solvent.

Citation Information

Patent Citations

  • Glass powder, back silver paste for high-performance PERC cells and preparation method thereof

    CN114656154B

Cited By

  • Modified glass powder for TOPCon battery fine grid and preparation method of modified glass powder

    CN120483531A